Experiencias Del Cuerpo, en Tres Jóvenes con Vih de la Ciudad De Bogota, un Analisis Desde sus Narrativas (2016)
The present investigation discusses the experiences that they establish with their intimate and social body of HIV-positive people, from the theory of Holons, passing through the subjectivities of the body, emotional ties and factors complementary such as the life project, notions of death and self-care. The participants in this research are men with more than a year of diagnosis, 24 to 32 years of age, currently undergoing antiretroviral treatment in the city of Bogotá.